Selected Histone Deacetylase Inhibitors Reverse the Frataxin Transcriptional Defect in a Novel Friedreich’s Ataxia Induced Pluripotent Stem Cell-Derived Neuronal Reporter System - Schreiber, Anna M.; Li, Yanjie; Chen, Yi-Hsien; Napierala, Jill S.; Napierala, Marek (Frontiers in Neuroscience, 2022)
Friedreich’s ataxia (FRDA) is a neurodegenerative disorder caused by expansion of GAA repeats within the first intron of the frataxin (FXN) gene. The location and nature of the expansion has been proven to contribute to transcriptional repression of FXN by decreasing the rate of polymerase II (RNAPII) progression and increasing the presence of histone modifications associated with a heterochromatin-like state. Targeting impaired FXN transcription appears a feasible option for therapeutic intervention, while no cure currently exists. We created a novel reporter cell line containing a FXN-Nanoluciferase (FXN-NLuc) fusion in induced pluripotent stem cells (iPSCs) reprogrammed from FRDA patient fibroblasts, thus allowing quantification of endogenous FXN expression. The use of iPSCs provides the opportunity to differentiate these cells into disease-relevant neural progenitor cells (NPCs). NPCs derived from the FXN-NLuc line responded to treatments with known FXN inducer, RG109. Results were validated by quantitative PCR and western blot in multiple FRDA NPC lines. We then screened a commercially available library of compounds consisting of molecules targeting various enzymes and pathways critical for silencing or activation of gene expression. Only selected histone deacetylase inhibitors (HDACi) were capable of partial reactivation of FXN expression. This endogenous, FRDA iPSC-derived reporter can be utilized for high throughput campaigns performed in cells most relevant to disease pathology in search of FXN transcription activators.